The Interaction of Gut Microbiota Composition and Dietary Starch Form on Gut Health in Aged Mice. (29th May 2020) - Smith, Kelsey; Francisco, Sarah; Zhu, Ying; Tsai, Chia-Fang; Barger, Kathryn; Smith, Donald; Greenberg, Andrew; Taylor, Allen; Rowan, Sheldon
Abstract: Objectives: A high glycemic diet has been shown to increase gut permeability, which is associated with increased disease risk. Our objective was to evaluate the role of gut microbiota in mediating the relationship between dietary starch composition and gut health. Methods: A high (HG) or low glycemic (LG) diet was fed in equal amounts to male mice from 12 to 24 months of age. The diets differed only by starch composition, which was 100% rapidly-digested amylopectin in the HG diet or 30% amylopectin/70% amylose in the LG diet. Within each diet, mice were assigned to one of three treatment conditions: continuous broad-spectrum antibiotic treatment (ampicillin and neomycin; HGabx or LGabx), weekly fecal microbiota transplants (FMT) from donor control mice fed the alternate diet (HG[tLG] or LG[tHG]), or a control group receiving no additional treatment. Feces were collected for microbiome analysis. Colon sections were collected for histology. Results: The diet affected gut microbiota composition, with significantly greater abundance of Clostridium, Ruminococcus, and Coprobacillus in the HG-fed control animals compared with LG-fed controls. Antibiotic treatment in HG-fed animals resulted in elimination of Bacteroidetes and most Firmicutes and a proliferation of Proteobacteria, whereas LG-fed animals were able to maintain Bacteroidetes and a lower abundance of Proteobacteria. Fecal microbiota transplants altered the gut microbiome and recipients differed from their donors. Histological evaluation of colons showed increased intestinal disease in HG-fed animals across all treatments, including increased inflammatory cell infiltration and abnormal villi. Antibiotic treatment in HG-fed animals resulted in the most severe disease phenotype, and most animals died within 4–6 months on treatment and presented with an enlarged and hemorrhagic cecum upon necropsy. Conclusions: The high glycemic diet altered the gut microbiome and increased the prevalence of pathological intestinal morphology, which was further exacerbated with antibiotic treatment. Our work suggests that dietary starch form has a substantial effect on the gut health outcomes, particularly in the context of antibiotic treatment or fecal microbiota transplants. Funding Sources: BrightFocus Foundation, USDA/NIFA AFRI, USDA, Stanley N. Gershoff Scholarship, NIH RO1, Thome Memorial Foundation.